Attitudes and actions of participants in multi-stakeholder processes and platforms - Varma, Samyuktha; Evans, Alexandra E.V.; Silva Wells, C.da; Jinapala, K. (Informa UK Limited, 2009)
Multi-stakeholder processes (MSPs) and platforms are being used to address various aspects of water management. They have been championed as a way to improve planning and coordination to involve marginalized groups, and to increase learning and uptake of innovations. Between 2005 and 2008, a project called 'WASPA Asia' established multi-stakeholder platforms in two cities, Kurunegala in Sri Lanka and Rajshahi in Bangladesh, to address wastewater use in agriculture and its impact on farmers' livelihoods. This paper presents findings on the benefits and constraints of a particular MSP around a 'Learning Alliance'. It also describes and analyzes the methodology used to obtain findings and suggests ways in which such a methodology could be used to improve results of MSPs. The paper indicates that the obvious merit of MSPs is in providing spaces for information sharing and awareness-raising. In time, MSPs can evolve to bring about changes in stakeholders' attitudes and actions but in many cases they are established around short-term projects, which limits their potential for (institutional) change. Given this constraint, attitudinal change and a better understanding of the issues amongst stakeholders are major accomplishments. Analysis of the methodology used for the review shows the benefits of regular joint monitoring, open communication, and the usefulness of relatively simple tools such as 'change stories'.